A Heterodimeric Antibody Fragment for Passive Immunotherapy Against Norovirus Infection. (25th March 2020) - Yuki, Yoshikazu; Kurokawa, Shiho; Sato, Shintaro; Sasou, Ai; Matsumoto, Naomi; Suzuki, Akio; Sakon, Naomi; Goda, Yuki; Takeyama, Natsumi; Miyoshi, Tatsuya; Marcotte, Harold; Tanaka, Tomoyuki; et al.
Abstract: Human noroviruses cause an estimated 685 million infections and 200 000 deaths annually worldwide. Although vaccines against GII.4 and GI.1 genotypes are under development, no information is available regarding vaccines or monoclonal antibodies to other noroviral genotypes. Here, we developed 2 variable-domain llama heavy-chain antibody fragment (VHHs) clones, 7C6 and 1E4, against GII.4 and GII.17 human noroviruses, respectively. Although 7C6 cross-reacted with virus-like particles (VLPs) of GII.17, GII.6, GII.3, and GII.4, it neutralized only GII.4 norovirus. In contrast, 1E4 reacted with and neutralized only GII.17 VLPs. Both VHHs blocked VLP binding to human induced pluripotent stem cell-derived intestinal epithelial cells and carbohydrate attachment factors. Using these 2 VHHs, we produced a heterodimeric VHH fragment that neutralized both GII.4 and GII.17 noroviruses. Because VHH fragments are heat- and acid-stable recombinant monoclonal antibodies, the heterodimer likely will be useful for oral immunotherapy and prophylaxis against GII.4 and GII.17 noroviruses in young, elderly, or immunocompromised persons. Abstract : We developed a heterodimeric llama heavy-chain antibody fragment that simultaneously neutralizes GII.4 and GII.17 human noroviruses. This heterodimer may offer a novel oral antibody therapy for preventing and treating disease symptoms due to GII.4- and GII.17-genotype norovirus infection.